Assessment of intraductal carcinoma in situ (DCIS) using grating-based X-ray phase-contrast CT at conventional X-ray sources: An experimental ex-vivo study - Hellerhoff, Karin; Birnbacher, Lorenz; Sztrokay-Gaul, Aniko; Grandl, Susanne; Auweter, Sigrid; Willner, Marian; Marschner, Mathias; Mayr, Doris; Reiser, Maximilian F.; Pfeiffer, Franz; Herzen, Julia (PLoS ONE, 2019)
Background The extent of intraductal carcinoma in situ (DCIS) is commonly underestimated due to the discontinuous growth and lack of microcalcifications. Specimen radiography has been established to reduce the rate of re-excision. However, the predictive value for margin assessment with conventional specimen radiography for DCIS is low. In this study we assessed the potential of grating-based phase-contrast computed tomography (GBPC-CT) at conventional X-ray sources for specimen tomography of DCIS containing samples. Materials and methods GBPC-CT was performed on four ex-vivo breast specimens containing DCIS and invasive carcinoma of non-specific type. Phase-contrast and absorption-based datasets were manually matched with corresponding histological slices as the standard of reference. Results Matching of CT images and histology was successful. GBPC-CT showed an improved soft tissue contrast compared to absorption-based images revealing more histological details in the same sections. Non-calcifying DCIS exceeding the invasive tumor could be correlated to areas of dilated bright ducts around the tumor. Conclusions GBPC-CT imaging at conventional X-ray sources offers improved depiction quality for the imaging of breast tissue samples compared to absorption-based imaging, allows the identification of diagnostically relevant tissue details, and provides full three-dimensional assessment of sample margins.
CRIS-Team Scopus Importer:2023-03-08